TAHAP PENGETAHUAN DAN PELAKSANAAN PAKEM GURU BAHASA ARAB MADRASAH IBTIDAIYAH (MI) DI ACEH - Hayati, Salam (PIONIR: Jurnal Pendidikan, 2016)
This study examined the level of knowledge and implementing of PAKEM among Arabic language teachers in Madrasah Ibtidaiyah in Aceh Province. The study imployed a survey research design which involved 208 Arabic teachers in Madrasah Ibtidaiyah from three cities in Aceh Province. Test instrument and questionnaires were administered to the respondents, and descriptive statistics were employed analyses the data. The findings showed that Arabic teachers have a good level of PAKEM knowledge and a high level of implementing of PAKEM approach.